Hematology of Kids of Different Genotypes Indicators - M. A, Huseinova; B. H., Djambilov; F. E., Sherqulova (European Journal of Life Safety and Stability (2660-9630), 2021)
The article provides data on the study of the clinical and biochemical parameters of the blood of goats of the local breed of Uzbekistan and their crosses of the 1st and 2nd generations, obtained from crossing them with the Russian white breed. It was found that crossbred kids surpassed their peers of the local breed in the number of erythrocytes, leukocytes and platelets, and the amount of hemoglobin was higher in hybrids of the 1st generation by 3.6 g / l (3.3%); II generation - by 4.51 g / l (4.0%) in comparison with similar indicators of local kids. Morphobiochemical blood parameters of kids in all experimental groups were within physiological norms.